Simulation of photovoltaic station interfacing scada within transmission line - Zamzami Zamzami; Nelly Safitri; Muhammad Arhami; Naziruddin Naziruddin (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In this paper, a developed simulation of a photovoltaic (PV) station that includes a PV module, a grid-connected inverter, a maximum power point tracking (MPPT) system, and a DC link capacitor was discussed. The MPPT uses a proportional integral derivative (PID) incremental conductance controller. Due to make it simple to control and monitor the PV station, Simulink dashboard is used to develop an interface that resembles a supervisory control and data acquisition (SCADA) system. Then the faults circumstances were simulated on one of the circuits of the double circuit transmission line using the faults combo box that is accessible in the interface. Then the cases were developed to examine the impact of various faults on the operation and control of the solar station. The developed cases namely normal circumstance, single-phase to ground fault circumstance, double-phase fault circumstance, and three-phase to ground fault circumstance, respectively. Three-phase voltage and current at given fault conditions have been measured to control voltage sag and swell. The active and reactive power are also measured due to obtain that they are injected or absorbed the power from and to the transmission line and maintain toward their setpoint values as indications while the faults occurred.